Exogenous Hydrogen Sulfide Offers Neuroprotection on Intracerebral Hemorrhage Injury Through Modulating Endogenous H2S Metabolism in Mice - Shan, Haiyan; Qiu, Jianping; Chang, Pan; Chu, Yang; Gao, Cheng; Wang, Haocheng; Chen, Guang; Luo, Chengliang; Wang, Tao; Chen, Xiping; Zhang, Mingyang; Tao, Luyang (Frontiers in Cellular Neuroscience, 2019)
Hydrogen sulfide (H2S), a novel gaseous mediator, has been recognized as an important neuromodulator and neuroprotective agent in the central nervous system. The present study was undertaken to study the effects of exogenous H2S on intracerebral hemorrhage (ICH) and the underlying mechanisms. The effects of exogenous H2S on ICH were examined by using measurement of brain edema, behavior assessment, injury volume, propidium iodide (PI) staining, and Western blotting, respectively. ICH induced significant downregulation of endogenous H2S production in the brain, which may be the result of decreasing in CBS, the predominant cerebral H2S-generating enzyme. Administration of sodium hydrosulfide (NaHS), a classical exogenous H2S donor, not only restored brain CBS expression and H2S content but also attenuated brain edema, improved motor performance and ameliorated performance in Morris water maze test after ICH. Immunoblotting results showed that H2S pretreatment reversed ICH-induced cleavage of caspase-3 and decline of Bcl-2, suppressed LC3-II and Beclin-1 activation and maintained p62 level in injured striatum post ICH. However, H2S could not restore brain CBS expression and H2S content, reduce brain edema and improve motor performance and memory function after ICH through modulating autophagy and apoptosis when pretreated with the CBS inhibitor, aminooxyacetic acid (AOAA). We also found that AOAA reduced the endogenous H2S production through inhibiting the enzyme activity of CBS rather than modulating the expression of CBS protein level. These results suggest a protective effect and therapeutic potential of H2S in the treatment of brain injury after ICH and the protective effect of exogenous H2S against ICH may be not a direct action but an indirect effect through inducing endogenous H2S metabolism responses.